PELAKSANAAN KEWENANGAN MAJELIS PENDIDIKAN DAERAH KABUPATEN BENER MERIAH TERHADAP PENENTUAN KEBIJAKAN DAERAH DALAM BIDANG PENDIDIKAN DI KABUPATEN BENER MERIAH - Aini, Quratul; Mukhlis, Mukhlis; Yusrizal, Yusrizal (Suloh: Jurnal Fakultas Hukum Universitas Malikussaleh, 2025)
The birth of the Regional Education Council (MPD) institution was based on the Authority of the Aceh Government as regulated in Aceh Qanun Number 03 of 2006 concerning the organizational structure and work procedures of the Aceh regional education council. The Regional Education Council in Bener Meriah Regency is an independent institution and not an implementing element of the Regional Government and DPRK, it is a forum for increasing the role of education in the development of Bener Meriah Regency. This research aims to analyze the implementation of authority to determine regional policies as well as the obstacles between the Regional Education Council and the Bener Meriah Regency Government in implementing policies in education in Bener Meriah Regency.This research uses an empirical juridical method, qualitative research type, this research is descriptive, with the research location in Bener Meriah Regency, the location is the Regional Education Council. Data collection sources consist of primary data and secondary data, observation and interview data collection tools, research results are arranged systematically to obtain clarity on the problems to be researched.Based on the research results, it shows that the Bener Meriah Regional Education Council, as a government agency, often encounters problems that can more or less affect the work system within the agency, both in carrying out programs and in other matters. However, despite all the shortcomings and limitations, several programs that have been planned have received real results in accordance with the desired expectations. This achievement will also be a stimulus for other employees to improve their performance so that all the programs that have been planned can be implemented well.It would be better for the Bener Meriah government to produce the latest Qanun, especially to regulate the MPD in the Bener Meriah Regency government so that they have more authority and can work together stronger. Also, MPD should give consideration to the government, then develop a concept for guidance and control of education implementation.